2020
DOI: 10.1111/gbb.12689
|View full text |Cite
|
Sign up to set email alerts
|

Do gene expression findings from mouse models of cocaine use recapitulate human cocaine use disorder in reward circuitry?

Abstract: Animal models of drug use have investigated possible mechanisms governing human substance use traits for over 100 years. Most cross‐species research on drug use/addiction examines behavioral overlap, but studies assessing neuromolecular (e.g. RNA) correspondence are lacking. Our study utilized transcriptome‐wide data from the hippocampus and ventral tegmental area (VTA)/midbrain from a total of 35 human males with cocaine use disorder/controls and 49 male C57BL/6J cocaine/saline administering/exposed mice. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…However, equally interesting is the possibility that these two groups may achieve a similar behavioral phenotype through different mechanisms. For instance, the enrichment of dopaminergic synapse-related genes has been the major finding reported by previous studies, again largely performed in males (79,80). While our data confirm that dopaminergic pathway is shared across sex we still see important male-specific chromatin changes in genes encoding dopamine receptors, which are likely important for sex-specific cocaine-induced responses and could have not been anticipated by earlier, male-focused studies.…”
Section: Discussionsupporting
confidence: 67%
“…However, equally interesting is the possibility that these two groups may achieve a similar behavioral phenotype through different mechanisms. For instance, the enrichment of dopaminergic synapse-related genes has been the major finding reported by previous studies, again largely performed in males (79,80). While our data confirm that dopaminergic pathway is shared across sex we still see important male-specific chromatin changes in genes encoding dopamine receptors, which are likely important for sex-specific cocaine-induced responses and could have not been anticipated by earlier, male-focused studies.…”
Section: Discussionsupporting
confidence: 67%
“…Another issue is that there is no certain way to cross-map animal and human phenotypes, limiting the opportunities for translation. However, as a recent proof of principle, one study (Huggett, Bubier, Chesler, & Palmer, 2020 c ) found modest but significant overlap in differentially expressed genes and gene networks when comparing human CocUD case–control data with mice in a cocaine v. saline solution self-administration paradigm, suggesting commonalities in the reward circuitry of human CocUD and self-administration paradigms in rodents.…”
Section: Conclusion and Future Prioritiesmentioning
confidence: 99%
“…Convergent gene expression changes between animal and human studies have highlighted pathways and biological processes that may be relevant for CUD, including the ERK/MAPK signaling pathway, long-term potentiation, synaptic plasticity (synucleins), and mitochondrial function [103]. Other studies have used the data generated by the above-mentioned studies in humans to assess convergence of gene expression mechanisms with rodents, highlighting genes involved in dopamine and serotonin function such as SLC1A2, CALM3, ALDOA, ALDOC, and ENO2 [104] and in brain plasticity like APP, GRIN2A, GRIN2B, KCNA2, MAP4, PCDH10, PPP3CA, SNCB, and SV2C [105].…”
Section: Transcriptomic Studiesmentioning
confidence: 99%